2010
DOI: 10.1111/j.1476-5381.2010.01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic analysis of pralidoxime after its intramuscular injection alone or in combination with atropine‐avizafone in healthy volunteers

Abstract: BACKGROUND AND PURPOSETreatment of organophosphate poisoning with pralidoxime needs to be improved. Here we have studied the pharmacokinetics of pralidoxime after its intramuscular injection alone or in combination with avizafone and atropine using an auto-injector device. EXPERIMENTAL APPROACHThe study was conducted in an open, randomized, single-dose, two-way, cross-over design. At each period, each subject received either intramuscular injections of pralidoxime (700 mg), or two injections of the combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Although these investigators found that the goodness-of-fit of this alternative model was lower than their original model, other authors have found it useful to fit the i.m. absorption kinetics of several other aqueous drug products such as trovafloxacin [30], pralidoxime [31], or recombinant human luteinizing hormone [32]. Another possible modification is to use two asynchronous inverse-gaussian absorption processes, a strategy that successfully quantified the effect of adrenaline on the uptake of ropivacaine in a thoracic paravertebral or a femoral nerve block [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Although these investigators found that the goodness-of-fit of this alternative model was lower than their original model, other authors have found it useful to fit the i.m. absorption kinetics of several other aqueous drug products such as trovafloxacin [30], pralidoxime [31], or recombinant human luteinizing hormone [32]. Another possible modification is to use two asynchronous inverse-gaussian absorption processes, a strategy that successfully quantified the effect of adrenaline on the uptake of ropivacaine in a thoracic paravertebral or a femoral nerve block [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Clearance (CL) was estimated by dividing the administered dosage by AUC 0- ∞ . AUC and C max of DXM and nefopam administered alone or in combination were log-transformed and compared using a confidence interval (CI) approach [13]. The nonparametric test (Wilcoxon test) was used for statistical evaluation of t max of the two treatments.…”
Section: Methodsmentioning
confidence: 99%
“…An important consideration when combination therapies are used is the potential for drug-drug interactions [12,13]. Preclinical pharmacokinetic studies are needed in order to maximize both efficacy and safety in clinical trials of combination therapies for TBI [14].…”
Section: Introductionmentioning
confidence: 99%
“…[23,24] But most frequently ion pair chromatography (IPC) coupled to electrochemical detection (ECD), [25,26] radio detection (RD), [27] and UV detection [14,28,29] has been applied. [30] Although more modern RPC-tandem mass spectrometric (RPC-MS/MS) methods provide better sensitivity and selectivity, [23,24] UV-detection appears to be sufficient for the quantification of high micromolar 2-PAM concentrations present in plasma and urine samples. [30] Although more modern RPC-tandem mass spectrometric (RPC-MS/MS) methods provide better sensitivity and selectivity, [23,24] UV-detection appears to be sufficient for the quantification of high micromolar 2-PAM concentrations present in plasma and urine samples.…”
Section: Introductionmentioning
confidence: 99%
“…For a detailed overview, see the review on 2-PAM quantification in this issue. [12][13][14]20,[23][24][25][26][27] In general, reports of quantitative urine analysis are quite rare, covering only 2-PAM concentrations in rats by IMAC-UV [19] and IPC-RD [27] and in humans by CZE-UV. [12][13][14]20,[23][24][25][26][27] In general, reports of quantitative urine analysis are quite rare, covering only 2-PAM concentrations in rats by IMAC-UV [19] and IPC-RD [27] and in humans by CZE-UV.…”
Section: Introductionmentioning
confidence: 99%